38 Immune evasion of HPV-associated HNSCC. Issue 5 (May 2015) - Reuschenbach, M.
Abstract : Background: The immune system is recognized as an important player during development and progression of human papillomavirus (HPV)-induced cancers. While on the one hand a sufficient effector immune response is discussed to represent an important contributor to regression, immune evasion is suggested to contribute to progression. Previously we characterized the tumor tissue of oropharyngeal cancers (OPSCC) for characteristics potentially contributing to either an effective immune response or to immune evasion, including alterations in antigen presentation (HLA class I heavy chain and β 2-microglobulin) and infiltration with T cells of effector or suppressor phenotype. HPV-associated cancers were characterized by frequent complete loss of HLA class I heavy chain and β 2-microglobulin expression and dense infiltration with Foxp3-expressing cells indicating potentially suppressive regulatory T cells. Since HLA class I loss as well as regulatory T cells may be important modulators against an effective immune response, therapeutic counter-regulation could be considered. Material and methods: In order to test different interventions, we have been developing autologous in vitro systems. One cell line was successfully established from an HPV-associated OPSCC and peripheral blood from the patients was collected. CD107 degranulation assays were used to study cytotoxic effects of different immune cell populations when incubated with the tumor cells. Results: Tumor cells from this patient were HLA class I proficient. While neither NK cells nor T cells led to a marked cytotoxic effect, depletion of CD25-positive T cells (regulatory T cells) increased CD107 degranulation. Conclusions: The results point to an immuno suppressive contribution of regulatory T cells in OPSCC patients. Further models will be used to study the mechanisms and effects of other immune evasion phenomena, including the loss of HLA class I expression observed in tumor tissue.